MODERN METHODS OF DETERMINING OF THE MOMENTS WATER QUALITY.COMPARING THE RESULTS WITH TRADITIONAL METHOD - Angelov, Plamen; Rankov, Maya; Vuchkov, Borislav (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Hydrometric propeller methods, is device that responds and measuring the velocity of the water current at the point where its sensor axis is located. Mechanical hydrometric propellers are widely used in our country, in which the current causes rotation of a screw vane with an angular velocity proportional to the velocity of the current, in this method the depth of the river profile must be taken into account in order to comply with the measurement condition in 1, 2, or 3 points namely 0.2h, 0.6h and 0.8h, h-depth of flow [2]. In the present topic, a comparison will be made between a hydrometric propeller, a device for measuring speeds and depths based on the principle of magnetic induction. Graphs, tables and conclusions from field measurements will be presented. The device will be compared measures water velocity by using Faraday's principle of magnetic induction. This allows measurement of low velocities without rotating parts. The research will help solve problems during operational work (field work), will aim to show fast, accurate results in determining water quantities, shortening measurement time, using the device at low water levels, at small flows.